2018
DOI: 10.1080/07434618.2018.1470668
|View full text |Cite
|
Sign up to set email alerts
|

The effects of literacy interventions on single-word reading for individuals who use aided AAC: a systematic review

Abstract: The purpose of this systematic review was to investigate the effects of instruction on single-word reading of individuals who use aided augmentative and alternative communication (AAC). A systematic search identified nine single-case experimental design studies that involved 24 individuals who used aided AAC. Overall, the evidence indicated that instruction had positive effects on reading at the single-word level for individuals across ages and diagnostic categories (i.e., autism spectrum disorder (ASD), cereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…In the cerebral palsy field, there is a shift towards actively recommending and testing these cognitive interventions with children with cerebral palsy. Our review found newer evidence of literacy interventions tailored for children with cerebral palsy using communication devices were effective (green light) [117,118]. Infants that received GAME intervention (a combination of motor training, environmental enrichment, and coaching) had better cognition at 1 year of age than age-matched peers on a norm-referenced test (yellow light, weak positive) [83,84].…”
Section: Cognitive Interventionsmentioning
confidence: 99%
“…In the cerebral palsy field, there is a shift towards actively recommending and testing these cognitive interventions with children with cerebral palsy. Our review found newer evidence of literacy interventions tailored for children with cerebral palsy using communication devices were effective (green light) [117,118]. Infants that received GAME intervention (a combination of motor training, environmental enrichment, and coaching) had better cognition at 1 year of age than age-matched peers on a norm-referenced test (yellow light, weak positive) [83,84].…”
Section: Cognitive Interventionsmentioning
confidence: 99%
“…Being able to read and write enables individuals to access and process information, to communicate and to make informed choices. AAC technology has been used to not only support people overcoming this barrier but also to assist the individuals to develop literacy skills (Allena et al, 2017;Mandak et al, 2018).…”
Section: Identified Priority Clinical Training Need: the Use Of Technologymentioning
confidence: 99%
“…It has been reported that up to 90% of individuals with congenital CCN struggle to acquire functional literacy (Foley and Wolter 2010), despite an acknowledgement that literacy acquisition is of critical importance for people with CCN (Mandak et al 2018). In addition, people with acquired cognitive impairments, e.g., aphasia resulting from a stroke (cerebral vascular accident), also experience varying degrees of difficulty with both expressive and receptive written language.…”
Section: Literacy Skills Vocabulary Organization and Training Requirmentioning
confidence: 99%
“…The importance of introducing literacy programmes for all children with CCN, regardless of assumed intellectual impairment, has been championed by many practitioners (Smith 2005, Mandak et al 2018. Despite evidence that speech output supports literacy learning (Schlosser 2003), AAC technology has yet to be designed to: (1) support ways in which pre/non-literate users can access vocabulary not in their systems; and (2) bridge the transition between symbol based AAC and literacy in a progressive manner without having to change systems.…”
Section: Literacy Skills Vocabulary Organization and Training Requirmentioning
confidence: 99%